CA single track microstructure simulation of nickel base alloy CM247LC and stainless steel S316L, including experimental validation of S316L. (1st February 2021) - Gerstgrasser, Marcel; Jakob, Raphael; Pandya, Kedar S.; Stirnimann, Josef; Wegener, Konrad
Abstract: Based on powder-bed fusion, a coupled cellular automata (CA) approach to simulate the microstructure and concentration distribution of two different materials, stainless steel S316 L and nickel base alloy CM247LC, in the middle and high scan speed range is presented. Local non-equilibrium models for rapid solidification are considered in this study and described. The simulation outputs from S316L and CM247LC are qualitatively and quantitatively compared with each other and validated with experiments in case of S316L. The melt pool geometry defines the grain morphology. Thin columnar grains and therefore a larger number can be found in the case of CM247LC compared to S316L. The temperature history, cooling rates and diffusivities have a tremendous impact on the grain morphology, based on SLM microstructure cross-section and single crystal simulations. Furthermore, concentration maps are analysed for both materials. In case of CM247LC, concentration maps are suggested as a possibility to predict hot cracks. Temperature dependent diffusivity coefficients and atomic spacing parameters are suggested. Simulations and experimental results are in good agreement. Graphical abstract: Unlabelled Image Highlights: A cellular automata approach to simulate the microstructure and concentration distribution of S316L and CM247LC with non-equilibrium models is presented Grains of CM247LC are thinner and the texture is more anisotropic compared to S316L The grain morphology is determined by the undercooling, cooling rate and solute diffusion The local higher concentrations of Al may predict intercrystalline hot cracks in case of CM247LC Simulations and experiments of S316L are in good agreement for the two laser scan speed parameters (middle and high range)